Character Education Behind the Function and Value of Cirebonan Tarling Art - Fajri, Khoirul; Sumiadi, Sumiadi; Sunendar, Dadang; Iskandarwassid, Iskandarwassid (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
A common problem encountered in the development of the art of tarling is the negative understanding of the majority of people about tarling itself. Tarling is currently experiencing difficulties in returning to be the belle of art in Cirebon society. As the development of tarling is used for the entertainment side and little by little reduces the value of tarling itself. This has become a fundamental problem for people who consider the art of tarling to be a mere art without any significant value. The purpose of this study was intended to find out more about character education in the function and value of the cirebonan tarling art. This research method uses descriptive qualitative exposure with ethnographic research design to find out more about character education in the function and value of the tarling itself, as well as using literature study data collection techniques related to Tarling arts and music, as well as interviews with informants. In general, tarling music can be divided into two forms: classical tarling music and modern Cirebon rhythm tarling music. Modern tarling experiences the absorption of various types of music, including pop and dangdut. Little by little in modern tarling puts forward the entertainment and material aspects and little by little reduces the value and function of the art of tarling itself. Whereas classical tarling music still has strong functions and values in instilling character education in every element of the performance of the tarling itself in each of its elements